2011
DOI: 10.1128/jvi.02675-10
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the Mannose-Specific Lectin, Griffithsin, to HIV-1 gp120 Exposes the CD4-Binding Site

Abstract: The glycans on HIV-1 gp120 play an important role in shielding neutralization-sensitive epitopes from antibody recognition. They also serve as targets for lectins that bind mannose-rich glycans. In this study, we investigated the interaction of the lectin griffithsin (GRFT) with HIV-1 gp120 and its effects on exposure of the CD4-binding site (CD4bs). We found that GRFT enhanced the binding of HIV-1 to plates coated with anti-CD4bs antibodies b12 and b6 or the CD4 receptor mimetic CD4-IgG2. The average enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 67 publications
4
57
0
1
Order By: Relevance
“…Of interest is the fact that VRC01p showed such consistent synergism with other entry inhibitors, suggesting multicomponent entry inhibition as a potential HIV prevention strategy. Presenting results similar to ours, Alexandre et al showed that another CD4bs-specific bnMAb b12 synergized with GRFT in neutralizing infectivity of a few viruses; this was associated with GRFT-mediated enhancement of viral binding to the MAb (62). On the other hand, to our knowledge, this is the first report showing CD4bs-specific bnMAb synergism with CCR5 antagonists and RT inhibitors.…”
Section: Discussionsupporting
confidence: 86%
“…Of interest is the fact that VRC01p showed such consistent synergism with other entry inhibitors, suggesting multicomponent entry inhibition as a potential HIV prevention strategy. Presenting results similar to ours, Alexandre et al showed that another CD4bs-specific bnMAb b12 synergized with GRFT in neutralizing infectivity of a few viruses; this was associated with GRFT-mediated enhancement of viral binding to the MAb (62). On the other hand, to our knowledge, this is the first report showing CD4bs-specific bnMAb synergism with CCR5 antagonists and RT inhibitors.…”
Section: Discussionsupporting
confidence: 86%
“…This allows a more tight interaction of the GRFTbound gp120 with the mAb b12, which may explain the synergistic activity. 39 It could therefore be possible that a similar mechanism of action is responsible for the observed synergy between MVN and the non-CBA mAb b12. Our generated HIV-1 NL4.3…”
Section: Discussionmentioning
confidence: 99%
“…Both T20 and b12 have been previously shown to act synergistically with other HIV-1 entry inhibitors (2,37,46,58). Thus, we next evaluated any possible synergistic effects of UCLA1 with T20 or b12.…”
Section: Resultsmentioning
confidence: 99%
“…The synergy was quantified and expressed as a combination index (CI) using the IC 50 s (8). Calculation of the CI was based on the Chou-Talalay equation: CI ϭ (D) 1 /(Dx) 1 ϩ (D) 2 /(Dx) 2 , in which (Dx) 1 and (Dx) 2 in the denominators are the concentrations of agent 1 and agent 2 alone that are required to neutralize the HIV-1 subtype C Env pseudovirus, and D 1 and D 2 in the numerators are the concentrations of agent 1 and agent 2 when used in combination that also neutralize the virus. A CI value of less than 1, equal to 1, or more than 1, indicates synergism, an additive effect, and antagonism, respectively (8,59).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation